Bioarchaeological analysis of the human skeletal remains from cliff tomb burial of the Wangyuancun site in Leshan, Chengdu Plain, Southwest China - Zhang, Yan; Zhou, Kehua; Jin, Guolin; Yong, Huaisong; Tang, Fei (Frontiers in Earth Science, 2023)
Though archaeological and historical-document evidences for the cliff necropolises in ancient China were reported in literature, the bioarchaeological analysis for them is still absent. It is therefore the aim of this paper presents the first bioarchaeological analysis for the skeletal samples of cliff necropolises from the Iron Age in China. In this work, skeletal remains of 16 individuals (two males, three females, seven unsexed adults, one subadult, and three indeterminate sex and age individuals) of Wangyuancun site (on the border of the Chengdu Plain, China) were examined for the stature, dental pathologies, linear enamel hypoplasia, cribra orbitalia, degenerative osteoarthritis of the vertebrae and major joints, periostitis, trauma and other evidence of disease. The demographic structure of Wangyuancun site is characterized by a younger mean age at death and a low mortality rate for infants and children. The stature estimates show that these Iron Age people were similar in size compared with the people live in contemporary southwestern region of China. Most of the samples lacked indications of stress, but a few had cribra orbitalia, osteoarthritis, osteophytosis and various dental pathologies. Periosteal reactions were common, but the lesions are generally moderate or mild. These bioarchaeological results broaden our understanding of the health and lifestyle of the cliff tomb population of Chengdu Plain in the Iron Age. Our bioarchaeological examination of the skeletal samples of Wangyuancun site provides a rare opportunity to address questions concerning ancient people’s diet, health, disease and stress of population in the Iron Age of Chengdu Plain, Southwest China.